2015
DOI: 10.1089/mdr.2014.0226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of OmpK35, OmpK36 Porins, and Production of β-Lactamases on Imipenem Susceptibility in Klebsiella pneumoniae Clinical Isolates, Cairo, Egypt

Abstract: Imipenem MIC was markedly increased among K. pneumoniae isolates showing AmpC production with loss of both porins OmpK35/36. Meanwhile, the association of porin OmpK35/36 loss with ESBL production was not a direct cause of resistance to imipenem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…Recently, New Delhi Metallo β-lactamase (NDM) producing strains were emerging globally and such strains are difficult to treat due to its pan-resistance [10]. Currently, the strains are also resistant to clinically useful drugs such as imipenem and ceftazidime [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, New Delhi Metallo β-lactamase (NDM) producing strains were emerging globally and such strains are difficult to treat due to its pan-resistance [10]. Currently, the strains are also resistant to clinically useful drugs such as imipenem and ceftazidime [11]. …”
Section: Introductionmentioning
confidence: 99%
“…This resistance rate is greater than the study performed by Ghaith et al (2019), who found relatively lower frequencies of carbapenem-resistant K. pneumoniae (CRKP) between 43 and 56% in the same country. This difference is probably due to an increase in porin loss, leading to increased carbapenem resistance (Wassef et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-14, CTX-M-15, and SHV ESBL types were detected in P. aeruginosa and A. baumannii (Abdelkader et al, 2017; Alkasaby and El Sayed Zaki, 2017; Helmy and Kashef, 2017). Furthermore, as for AmpC production, CMY variants (CMY-2, CMY-42, CMY-102), DHA-1, EBC, FOX, and MOX were detected in clinical isolates of Enterobacteriaceae such as E. coli , K. pneumoniae , and P. mirabilis (Abdelaziz et al, 2013a; Helmy and Wasfi, 2014; Wassef et al, 2015).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%